Imagining Disarmament, Enchanting International Relations - Bolton, Matthew Breay. author. aut Link
XX, 133 p.
Keywords: “Brilliant and enchanting. . . Bolton has rekindled the magic in both theorizing IR and envisioning a world without weapons.” —Charli Carpenter, Professor of Political Science, University of Massachusetts Amherst, USA “A tour de force of creative thinking. Bolton prizes open new ways of thinking about disarmament, sensitive to the role of representation, imagination and characterisation.” —Alex Jeffrey, Reader in Human Geography, University of Cambridge, UK “The appeal of this enchanting book lies in crafting humanizing stories, artistically challenging the constrained imagination of disciplinary IR. ” —Ritu Mathur, Assistant Professor of Political Science and Geography, The University of Texas at San Antonio, USA “Matthew Bolton has produced an intriguing and provocative analysis of disarmament that weaves together social science and storytelling. He challenges you to transcend traditional, conservative, and patriarchal views of disarmament.” —Nick Ritchie, Lecturer in International Security, University of York, UK This book explores the global politics of disarmament through emerging international relations (IR) theories of discourse and imagination. Each chapter reflects on an aspect of contemporary activism on weapons through an analogous story from literary tradition. Shahrazade, convenor of the 1001 Nights, offers a potent metaphor for the humanitarian advocacy seeking to moderate the behaviour of violent people. The author reads Don Quixote in Cambodia’s minefields, reflects on Lysistrata at Greenham Common and considers how tropes in The Tempest were enrolled in both Pacific nuclear testing and efforts to resist it. The book draws on ethnographic fieldwork in communities affected by weapons and disarmament advocacy at the UN and calls for a re-enchantment of IR, alive toaffect, ritual and myth. Matthew Breay Bolton is Associate Professor of Political Science and Director of the International Disarmament Institute at Pace University, USA. Since 2014 he has worked on the UN advocacy of the International Campaign to Abolish Nuclear Weapons (ICAN), recipient of the 2017 Nobel Peace Prize.